A Câmara do FUNDEB do Conselho Municipal de Educação de Alta Floresta-MT : lemas e dilemas na atuação - Freire, Eduardo José (2016)
This study has as main objective to understand the functioning of the Chamber of Monitoring and Social Control of the Fund for Maintenance and Development of Basic Education and Valuing of the Education Professionals (CACS of the FUNDEB), of the municipality of Alta Floresta - MT. In the methodological perspective of dialectical historical materialism, we look to analyze the contradictions present in the actions of this Board and the political, economic and cultural movement in which it is inserted, for abstracting which limits and possibilities that the operation of this Chamber brings to the creation of a new culture of social control in the municipality in question. Authors, such as Gramsci (1981; 2006), Kosik (1976), Carnoy (2003), Semeraro (1999), Gohn (2008; 2012), Davies (1999; 2004; 2007; 2008; 2010; 2012), Siraque (2009), Silva (2011), Lima (2011) and Braga (2011; 2015), are part of the theoretical framework that allowed references to the use of important theoretical categories, such as: participation, social control and public policies. As methodological procedure, the used data collection instruments were: semi-structured interviews, questionnaires, observation and document analysis: the minutes of the researched Chamber meetings and official documents, such as the Internal Regulation of the Municipal Council of Education, the Municipal Laws n. 1.572/2007 and n. 1.666/2008, and the Federal Law n. 11.494/2007. The study results show up that the FUNDEB Chamber of Alta Floresta operates in bureaucratic format, in compliance with legislation. It presents weaknesses in terms of its functions, since we note limits in the functionality, as the hegemonic participation form of the Counselors, which is given as instrumental participation. This process presupposes transformation of the participation culture, especially, of the civil society representatives, to strengthen the social control that is attributed as primary function to the Board. What was found in this study is that in the municipality of Alta Floresta there are challenges for the Counselors of FUNDEB Chamber, the current ones and their successors, as regards to monitoring and social control of the applied resources in the municipal public system. It is worth stating that the scope of a quality public education, given the political and economic situation of the country, is something that depends on a collective project that is popular-ethical, and, in this studied case, we found that the lack of political discussion, the apathy of the civil society representatives to the treated technical subjects and the silencing of these segments require training in technical, accounting and political formation level, to give another direction to the deliberations of the Chamber, aiming to reach status of effective social control to his functioning.